An unexpected finding: The earliest record of cycad-like foliage in Gondwana - Cariglino, Barbara (2024)
Cycads (= Cycadophyta) are dioecious gymnospermous palm-like trees that bear a crown of typically pinnate leaves. They represent the most ancient lineage among living spermatophytes and are distributed today in tropical to temperate areas worldwide. Despite the fossil record of the group extends back to the Permian, pre-Mesozoic fossil evidence is almost exclusively found in strata from the Northern Hemisphere. In contrast, the undisputed Paleozoic presence in Gondwana is—to date—based only on the description of an anatomically preserved axis from the Kungurian (Permian) Iratí Formation in Brazil. Here, we present the earliest—and to our knowledge, the only known—evidence of cycad-like foliage from the Paleozoic of Gondwana. The specimen was recovered from the Guadalupian-aged Laguna Polina Member of the La Golondrina Formation (Permian, Santa Cruz Province, Patagonia Argentina), and belong to the Museo Padre Molina in Río Gallegos (MPM-PB). It consists of a part and counterpart impression of a pinnately compound leaf, with its apex and base unknown. Leaflets start small at the base and gradually increase in size along the length of the frond. Leaflets are perpendicularly attached to the rachis by their whole bases. Rachis is thick (~2 mm wide) and striated. Leaflets are quadrangular, larger than wide (ranging 24.3–43 mm long and 9.6–12 mm wide) and imbricated along the rachis. The leaflet bases have a slightly decurrent basiscopic margin in some segments, whereas the apexes are truncate to barely rounded. Thick veins run parallel along the leaflets’ margins from the rachis to the apex, rarely exhibiting bifurcations. The preservation strongly points to the attachment of the leaflets above instead of laterally to the rachis, potentially indicating this cycad-like foliage as a new species attributable to Nilssonia. If confirmed, then this would represent the oldest evidence for the genus worldwide.